Archeozoological materials of the Syganak settlement (according to the excavations of 2021) (Journal of history, 2023)
The article discusses results of the archaeozoological analysis of animal bone remains discovered in 2021 in the medieval hillfort of Syganak. The main purpose of the research work is to determine the features of the economy of the population of the settlement of Syganak in the 18-19 centuries. The osteological material of the first and second building horizons determined by the species composition and their quantitative composition is given. The archaeozoological study showed that 87.2% of the bones identified by animal species belong to domestic animals, and the share of wild animals is 12.8%. Among osteological materials 30.7% - are bones of small cattle. 26.4% of horse bones and 21.6% of cattle bones are in second and third places. Skeletal elements belonging to a camel make up 3.8%. The bones belonging to a dog are also approximately equal to the bones of a camel – 3.6%. Among wild animals, elements of the saiga skeleton predominate – 9.2%. Bones of other animals make up about – 1%. The results of morphometric examination of the bones of a number of domestic animals are presented in the form of graphical correlations. The archeozoological data of the Syganak hillfort were comparative analyzed with the results of archeozoological studies of the sites of Kultobe (Turkestan), Otyrar, Kultobe (Sozak district), Shymkent and Karatobe. The percentage of domestic ungulates in the farm is similar to the monuments described above. Comparative analysis of the sizes of metapodia of Syganak horses with measurements of metacarpal and metatarsal bones of horses found in the settlements of Kultobe and Shymkent was carried out. Biometric studies show that horses of the 16-19 centuries in the South Kazakhstan region had a height at the withers of about 144-136 cm.The work was carried out within the framework of the project of the Ministry of Science and Higher Education of the Republic of Kazakhstan No. BR10965310 «Comprehensive archaeological research of the object of historical and cultural heritage, the medieval settlement of Syganak».